PERAN GCG SEBAGAI MODERATING VARIABLE DARI PENGARUH EARNING MANAGEMENT TERHADAP NILAI PERUSAHAAN - Dewi Rosaria (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
This thesis examined the influence of Earning Management toward corporate value by exposing Corporate Governance as Moderating Variable. In this research, earning management as independent variable which is calculated using discretionary accrual (DAC). Researcher using Dechow model and regretted forward-looking model from cross sectional to define DAC. Corporate Value as dependent variable is represented by Tobin's Q, while Corporate Governance as Moderating Variable is indexed based on 18 items of exposure themes called Corporate Governance Perception Index. Researcher using 51 manufacture companies which are selected from 149 companies listed in Indonesia Stock Exchanges based on the defined criteria, with research timeframefrom the year of 2005 to 2008. The result of the research concluded that Earning management significantly influences corporate value; corporate governance practices influences the Earning management on the corporate value.